Hope and Creative Self-Efficacy as Sequential Mediators in the Relationship Between Family Socioeconomic Status and Creativity - Yang, Yinyinzi; Xu, Xiaobo; Liu, Wenling; Pang, Weiguo (Frontiers in Psychology, 2020)
This study examines how socioeconomic status (SES) predicts individual creativity through the mediating roles of hope and creative self-efficacy (CSE). Participants come from eight universities in the mainland China. Students’ socioeconomic status, hope, creative self-efficacy, and creativity were measured by the Socioeconomic Status Scale, the Adult Hope Scale, the Creative Self-efficacy Scale, and the Runco Ideational Behavior Scale. Correlational results showed that SES, creative ideation, hope, and creative self-efficacy were significantly and positively associated with each other. Path analyses revealed that hope and CSE played sequential mediating roles in the link between SES and creative ideation. These findings suggest that hope and CSE underlie the effect of SES on individuals' creative ideation.